Rapamycin is Effective for Upper but not for Lower Gastrointestinal Crohn’s Disease-Related Stricture: A Pilot Study - Zhong, Min; Cui, Bota; Xiang, Jie; Wu, Xia; Wen, Quan; Li, Qianqian; Zhang, Faming (Frontiers in Pharmacology, 2021)
Crohn’s disease (CD)-related fibrotic stricture remains a clinical challenge because of no effective treatments. This study aimed to evaluate the potential efficacy of rapamycin in patients with CD-related strictures in different locations in gastrointestinal tract. A pilot prospective study on using rapamycin for CD-related stricture was performed from April 2015 to August 2020 in a single center in China. Fifteen patients were enrolled into the study. The clinical efficacy was evaluated by diet score and gastrointestinal obstruction symptoms score. Clinical responses were defined as the ability to tolerate the regular diet with vegetable fiber combined with a reduction of ≥ 75% in overall target score and a score of less than two points for each item. Three patients discontinued rapamycin for less than 1-month due to intolerance to adverse events, then, 12 patients received ≥1 dose of the rapamycin and provided ≥1 post-baseline target score after baseline were included for intent-to-treat (ITT) analysis. 100% (5/5) of patients with upper gastrointestinal strictures achieved clinical response after using rapamycin. However, no clinical response was observed in those patients with CD lesions in lower gastrointestinal tract. Adverse events occurred in 40% (6/15) of patients. No death or serious opportunistic infections were observed in the present study. This study firstly raised the interesting hypothesis that rapamycin might be effective for CD-related stricture in the upper, but not in lower gastrointestinal tract.